The Role of the Translator in Conveying Pragmatic Meaning in Literary Texts - Ro'ziyeva Nilufar Jaxongirovna; Soliyeva M.A (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This study explores the crucial role of the translator in conveying pragmatic meaning in literary texts. Literary translation involves not only the accurate rendering of lexical and syntactic elements but also the interpretation of cultural, contextual, and pragmatic nuances embedded in the source text. Pragmatic meaning encompasses speech acts, implicature, politeness strategies, and culturally specific expressions, which often pose challenges for translators. Through analysis of selected literary excerpts, this research identifies common difficulties in transferring pragmatic meaning from one language to another and examines strategies employed by translators to preserve authorial intent and communicative effect. The study highlights the importance of pragmatic awareness, cultural competence, and interpretive skill in literary translation.